Synthesis of (tricyanofuran‐3‐ylmethylene)hydrazinyl thiazole‐containing chromophore: A study of its photophysical properties, solvatochromism, and TD‐DFT computations. (5th August 2022) - Pashameah, Rami A.; Alshareef, Mubark; Alharbi, Arwa; Alsoliemy, Amerah; Abumelha, Hana M.; Saad, Fawaz A.; El‐Metwaly, Nashwa M.
Abstract: The chromophore 2–2‐(3‐cyano‐5, 5‐dimethyl‐4‐((2‐[thiazol‐2‐yl]hydrazono)methyl)‐furan‐2(5 H )‐ylidene)malononitrile (TzHTCF ) was prepared by diazo‐coupling of diazotized 2‐aminothiazole with 3‐cyano‐2‐(dicyanomethylene)‐4, 5, 5‐trimethylfuran (TCF ). The TzHTCF absorption solvatochromism, in different polarity solvents, demonstrated a Δ E max = +4.74 in which the positive sign implied the occurrence of a red shift and the TzHTCF lowest excited state was more polar than its ground state. In addition, the TzHTCF fluorescence spectrum produced a λem in the 416–670 nm range and was more dependent on the solvent polarity than the absorption λmax, despite both exhibiting a red shift of 24 and 254 nm, respectively. To discover the Stokes shift ( ∆ ν ¯ ) behaviour of the TzHTCF derivative, Lippert–Mataga and linear solvation–energy relationship (LSER) formulations were utilized in which the LSER approach displayed better results than the Lippert–Mataga method ( R 2 = 0.9931). Furthermore, the LSER showed that the absorption and fluorescence solvatochromic behaviours were dependent on the solvent's hydrogen‐bond donor ( α ) and acceptor ( β ), along with the solvent's polarizability ( π *). Moreover, DFT calculations showed that TzHTCF has a planar configuration and its simulated absorption and emission spectra in dimethyl sulphoxide revealed that λmax primarily originated from the HOMO→LUMO and HOMO‐1→LUMO transitions, respectively. Abstract : The chromophore TzHTCF comprising thiazole and tricyanofuran was synthesized and its photophysical properties were analyzed. The fluorescence emission spectra presented one band, and a λem that had strong solvent dependence compared with the absorption λmax . The solvatochromism behaviour in terms of Lippert–Mataga plots and the linear solvation–energy relationship formulations was utilized.